I need help with factoring this expression.

X^2 + 2X + 48 =

X^2 + 2X + 1 = -47

( X + 1 ) ^2 +47 =

( X +1 + i √47) ( X +1 - i√47)

I need help with factoring this expression.

Tutors, please sign in to answer this question.

Woodland Hills, CA

X^2 + 2X + 48 =

X^2 + 2X + 1 = -47

( X + 1 ) ^2 +47 =

( X +1 + i √47) ( X +1 - i√47)

Olney, MD

x^{2} + 2x + 48

As written, the equation does not factor. In fact, using the quadratic formula, it has complex roots:

x = -1 ± i√47

If the equation is really x^{2} - 2x - 48, the factors are (x+6)(x-8)

If it's really x^{2} + 2x - 48, the factors are (x-6)(x+8)

- Algebra 2 3504
- Algebra 5068
- Math 9887
- Prealgebra 172
- Algebra Word Problem 2492
- Algebra Help 967
- Geometry 1907
- Math Help 5453
- Word Problem 5126
- Precalculus 1595

## Comments